Konstruksi Realitas Simbolik Pemimpin dalam Islam Melalui Program Damai Indonesiaku TVOne - Hakim, Lukman Al-; Rijal, Syamsul; Nur Rahman, Wildian Fajrin (Faculty of Da'wa and Communications Sciences, 2024)
The construction of symbolic reality of Damai Indonesiaku TVOne program has become a communication space for Islamic preaching that has an impact on people's perceptions of the reality of religious life. This article aims to examine the construction of symbolic reality of the meaning of a leader in Islam in Damai Indonesiaku TVOne program. This study uses the theory of social construction of reality by Peter L. Berger and Thomas Luckman and the construction of mass media by Burhan Bungin. This type of research is qualitative, constructivism paradigm with a phenomenological approach. The results of this study indicate that the symbolic construction of the meaning of a leader in Islam in Damai Indonesiaku program: first, externalization of the criteria for an ideal leader in Islam, such as: siddiq, tabligh, amanah, and fatonah. Second, objectivation of the objective reality of the symbol of the best leader in Islam, such as: Rasulullah SAW. Third, internalization, namely the interaction of the meaning of a leader in Islam that is manifested from the subjective process of Damai Indonesiaku program so that it has subjective meaning for individuals. The stages of the construction of symbolic reality of the Peaceful Indonesia program include: first, preparing construction materials by prioritizing commodity values and profits alone. Second, the distribution of construction through television and digital platforms on the @religiOne account. Third, the formation of reality construction by presenting visual images, religious music audio, lighting arrangements, to make it look attractive. Fourth, confirmation can be seen through television share-ratings or the number of subscribers and viewers through the @religiOne account. Fifth, consumer decisions that viewers will decide whether to become active viewers or just passive viewers.